On the practical experiences of the long-term athlete development programme of Hungarian swimming - Nagy, N.; Szemes, Á.; Szájer, P. (SPRINT - Sports Research Journal, 2024)
The success of Hungarian swimming is underpinned by a preparation and competition system that has been developed for many years, thanks to the professional group of the sports federation and the scientific and practical work of professionals in the sport. In our study, we aim to present the experiences of recent years regarding the domestic application of the Long-Term Athlete Development Program (LTAD) for swimmers. Our results indicate that there are several discrepancies between the application of the LTAD model for Hungarian swimmers and the expected theory. We believe that the success of Hungarian swimmers is partly due to maintaining the basic principles of the LTAD model and comparing it with other nations' swimming preparation plans, working within a system that includes unique elements to ensure the success of this small country.